The Tashbehs in Surat Al-Baqara Verses 1-18 and Its Education Implication - Ade Juang Eko Praseyo; Anwar, Saeful; Tamam, Abas Mansur; Alim, Akhmad (Formosa Journal of Multidisciplinary Research, 2024)
The aim of studying this topic is to know the implications of the tashbehs mentioned in Surah Al-Baqarah verses 1-18 related to the educational aspect. The study concluded that in Surah Al-Baqarah verses 1-18, there are methods of tashbehs, and they carry moral connotations related to the educational aspect. These indications can be extracted from methods and modalities used as a methodology for teaching. By using tashbehs in the education process, it will be better, because the education materials are easier to understand and stronger to influence. Also, the tashbeh methods enhances the emotional relationship between the teachers and the students, making the lessons more acceptable. Thus, it can be said that the use of tashbeh as an advocacy tool has a positive impact on education.